Eksistensi Kalomba Di Tengah Arus Globalisasi Masyarakat Kajang Luar - Ari Reski Sashari; Syamsu Alam (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract This paper aims to describe the existence of Kalomba in the midst of globalization. In the global world, it is not only a process of cultural hegemonization, but it can provide opportunities for a plural and heterogeneous life to occur, even individuals and communities who are considered marginal are able to adapt in the midst of globalization. Local culture is not something that is backward and not modern, but local people are able to maintain their cultural ritual traditions and can respond to globalization by choosing and sorting out what must be accepted, adapted and what must be rejected. The results of this study indicate that the kalomba which was held a hundred years ago, which was originally carried out by Karaeng Padulu Daeng Seroang, has undergone changes in terms of cultural rituals slowly, especially in the current era. Kalomba has been touched by the modern ritual procession or the level of originality of the ritual is slowly fading away, as in the facilities and infrastructure used due to the globalization factor. However, this is a form of creative transformation of the Kajang Luar community so that their traditions still exist in the midst of globalization. Keywords: Existence, Kalomba, Ritual, Globalization